Hemostatic abnormalities in adult patients with marfan syndrome - Kornhuber, Katharina T.; Seidel, Heide; Pujol, Claudia; Meierhofer, Christian; Roeschenthaler, Franz; Pressler, Axel; Stoeckl, Alexander; Nagdyman, Nicole; Neidenbach, Rhoia Clara; Von Hundelshausen, Philipp; Halle, Martin; Holdenrieder, Stefan; et al. (Cardiovascular Diagnosis and Therapy, 2019)
Background: Aortic root ectasia might induce hemostatic disorders in patients with Marfan syndrome (MFS) via altered blood flow and rheology. The aim of this study was to explore the hemostasis in patients with MFS compared with healthy controls. Methods: In this cross-sectional case-control study we included patients with verified MFS (n=51) and sex- and age-matched healthy controls (n=50). Main criteria were the aortic root in echocardiography and cardiac magnetic resonance imaging (MRI), and the coagulation status. Results: When compared with healthy controls, patients with MFS showed significantly increased diameters of the aortic roots (43.0±7.72 vs. 28.8±3.74 mm, P<0.001) and aortic Z-scores (4.36±2.77 vs. 0.948±1.09, P<0.001), considerably higher values of Multiplate® tests (e.g., MP-ADP: 878.4±201.7 vs. 660.4±243.6 AU∗Min, P<0.001) and PFA-100® tests (PFA Col/ADP: 102.5±45.5 vs. 91.1±46.2 s, P<0.05), PTT (30.0±3.91 vs. 28.7±2.50 s, P<0.05) and D-dimers (0.488±0.665 vs. 0.254±0.099 mg/L, P<0.001). In MFS von Willebrand factor (VWF) activity (81.9%±41.8% vs. 106.3%±41.5%, P<0.05) and antigen (93.8%±43.9% vs. 118.8%±47.8%, P<0.05) and factor VIII activity (108.9%±29.6% vs. 126.7%±28.4%, P<0.05) were reduced. Significant positive correlations were found between aortic diameters and D-dimers (all P<0.05), as well as PFA Col/ADP (all P<0.01) in MFS patients. Factor VIII activity correlated significantly negatively with the diameter of the aortic root in MFS (r=-0.55, P<0.05). Conclusions: In conclusion, our study reveals hemostatic deviations in patients with MFS. Further studies are necessary to understand the causal relationship and the exact pathomechanism.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Aortic root dilatation; Coagulation; Marfan